Career management, organizational commitment and turnover intention: an empirical study on clinicians in public hospitals in China - Yu Shaoxuan (2019)
With the deepening of the medical reform in China, the unique long growth period of the medical industry and the rapid social and economic development in China lead to a significant conflict, which, in turn, increases the medical staff mobility. In fact, due to the prominent contradictions between doctors and patients and frequent incidents of malignant injuries to doctors, hospitals at all levels in China face the dilemma of doctors changing jobs or changing careers. The trend of medical staff shortage is increasingly conspicuous. With the rapid aging of the Chinese population and the increasing incidence of chronic diseases, medical and health services have become an important part of social services in China, exerting a direct impact on social stability. Therefore, paying attention to the turnover intention of medical staff has become a major issue deserving academic attention The subjects of this study are doctors from three hospitals in Guangzhou city, one of them a 3A level hospital (the highest level) and two 2A level ones. This study explores the impact of hospital organizational career management on the turnover intention of clinicians and examines the role of career growth and organizational commitment in the impact. Results show that the three variables of organizational career management, career growth and organizational commitment are positively correlated with each other and all of them are negatively correlated with turnover intention. As for the influence path, career growth and organizational commitment play a mediating role in the impact of career management on turnover intention. In addition, career growth plays a mediating role in the impact of career management on organizational commitment. It is also found that organizational career management, career growth, organizational commitment, and turnover intention have significant differences in some of the basic characteristics of clinicians. In terms of organizational career management, career growth, and organizational commitment, clinicians in level 3A hospitals score higher; in terms of turnover intention, clinicians in the level 2A hospitals score higher. In addition, clinicians with different characteristics such as age, marital status, and professional title have significant differences in organizational career management, career growth, organizational commitment, career growth, and turnover intention. Results of this study provide inspiration and suggestions for policy development of public health administrative departments and hospital management especially talent retention and offer guidance for further research. The findings of this study based on public hospitals in China may also contribute to enrich the literature in this field across the world.